(Re)configuring moral boundaries of intergenerational justice: the UK parent-led climate movement. Issue 12 (2nd December 2021) - Howard, Lisa; Howell, Rachel; Jamieson, Lynn
ABSTRACT : The interests of children in a climate-challenged future are under-represented within UK policy-making and public discourse. Debates on intergenerational equity have centred on economic logic rather than the moral issue of harms to the next generation, or the responsibilities of today's generation. Civil movements play an important role in changing public and political thinking on this issue; however, research on intergenerational climate justice activism has so far been confined to the youth movement. This study uses an in-depth diary and interview dataset of 20 UK-based activist mothers and fathers to explore the emotional spaces of parenting and campaigning for intergenerational climate justice. Attention was paid to the role of parenthood in the framing and motivation for action, and the way that campaigning was sustained or impeded by activist parents' personal relationships. The study found that the emotional spaces of activist parenting were managed and demarcated through moral boundary work that was used to define, distinguish and legitimise a collective representation. These boundaries were relational and drawn selectively to include similar others and to form bridges with politicians; boundaries also functioned to delegitimise the role of adults without children, and to exclude and excuse younger children and older relatives from playing a part in justice activism. The paper concludes by considering how these processes might impede the movement and have implications for wider social justice.